2010
DOI: 10.4088/jcp.09m05585ora
|View full text |Cite
|
Sign up to set email alerts
|

A Cohort Study of the Prevalence and Impact of Comorbid Medical Conditions in Pediatric Bipolar Disorder

Abstract: Neuropsychiatric (ie, ADHD, substance abuse, CNS disorders/epilepsy) and medical (ie, obesity, asthma, cardiovascular disease) disorders temporally precede the diagnosis of early-onset BD in pediatric patients and are associated with discrete facets of illness presentation, but they do not substantially alter the clinical course of the BD over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
2
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 0 publications
3
82
2
3
Order By: Relevance
“…The lack of evidence for an association between atopic illness and hypomanic symptoms is surprising given a number of cross-sectional studies (Goodwin et al 2003;Beyer et al 2005;Jerrell et al 2010) and longitudinal studies (Liang & Chikritzhs, 2013;Chen et al 2014;Lin et al 2014) have reported an association between asthma and bipolar disorder. This may be because previous studies have examined the severe end of the bipolar spectrum (hospitalization for bipolar disorder) and this association may not hold when our broad definition of hypomania is used.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of evidence for an association between atopic illness and hypomanic symptoms is surprising given a number of cross-sectional studies (Goodwin et al 2003;Beyer et al 2005;Jerrell et al 2010) and longitudinal studies (Liang & Chikritzhs, 2013;Chen et al 2014;Lin et al 2014) have reported an association between asthma and bipolar disorder. This may be because previous studies have examined the severe end of the bipolar spectrum (hospitalization for bipolar disorder) and this association may not hold when our broad definition of hypomania is used.…”
Section: Discussionmentioning
confidence: 99%
“…Psychotic symptoms have been reported in about one-third of youth with BD, and confer a significantly greater likelihood of lifetime GAD, agoraphobia, social phobia, and obsessive compulsive disorder (OCD) (236). Medical comorbidities including obesity, type 2 diabetes mellitus, other endocrine disorders, migraine headaches, central nervous system disorders ⁄ epilepsy, organic brain disorders ⁄ mental retardation, cardiovascular disorders, and asthma in a large cohort study were significantly more prevalent among children and adolescents with BD (n = 1841) compared to a control group (n = 4500) (237). In the COBY study (n = 348), overweight ⁄ obesity was seen in 42% of youth with BD, and was associated with increased psychiatric burden (238).…”
Section: Comorbidities and Mimicsmentioning
confidence: 99%
“…58 Moreover, these conditions, including obesity and T2DM, were found to precede diagnoses of BD. 54 Similarly, research based on medical claims data indicated that children and adolescents diagnosed with BD were more likely to access several medical services, including cardiology services. 55 Finnish population-based prospective data indicated that there was a bidirectional association between depressive symptoms and MetS between childhood (mean age, 12 years) and early adulthood (mean age, 33 years).…”
Section: Traditional Cardiovascular Risk Factors In Relation To Mdd Amentioning
confidence: 99%
“…[53][54][55][56][57] No published study could be identified that primarily sought to determine the prevalence of MetS in a pediatric MDD or BD population. Notwithstanding this, data from the South Carolina Medicaid program, covering all medical services and medication prescriptions between January 1996 and December 2005, indicated that children and adolescents with BD are differentially affected by several medical disorders, including but not limited to obesity and T2DM.…”
Section: Traditional Cardiovascular Risk Factors In Relation To Mdd Amentioning
confidence: 99%